Les transects photographiques : à la recherche des discontinuités dans le paysage - Morgane Flégeau (EchoGéo)
This article presents an exploratory method using photography as an analysis tool to understand landscape dynamics in the green belt of Paris Region. This method is considered as complementary to a mapping approach, developed at regional scale. Several transects are placed along radial segments across the green belt perimeter. The photographic database can be a way of analyzing landscape organization at local scale, to experience our study space and to bring a sensitive dimension, informing the access to the open spaces in a mostly peri-urban space.